Identifying growth hormone-regulated enhancers in the Igf1 locus - Alzhanov, Damir (Physiol Genomics, 2015)
Growth hormone (GH) plays a central role in regulating somatic growth and in controlling multiple physiological processes in humans and other vertebrates. A key agent in many GH actions is the secreted peptide, IGF-I. As established previously, GH stimulates IGF-I gene expression via the Stat5b transcription factor, leading to production of IGF-I mRNAs and proteins. However, the precise mechanisms by which GH-activated Stat5b promotes IGF-I gene transcription have not been defined. Unlike other GH-regulated genes, there are no Stat5b sites near either of the two IGF-I gene promoters. Although dispersed GH-activated Stat5b binding elements have been mapped in rodent Igf1 gene chromatin, it is unknown how these distal sites might function as potential transcriptional enhancers. Here we have addressed mechanisms of regulation of IGF-I gene transcription by GH by generating cell lines in which the rat Igf1 chromosomal locus has been incorporated into the mouse genome. Using these cells we find that physiological levels of GH rapidly and potently activate Igf1 gene transcription while stimulating physical interactions in chromatin between inducible Stat5b-binding elements and the Igf1 promoters. We have thus developed a robust experimental platform for elucidating how dispersed transcriptional enhancers control Igf1 gene expression under different biological conditions.